Peran Istri dalam Pengelolaan Keuangan Keluarga Perspektif Fiqh Muamalah dan Modernitas - Lidya Putri, Nyimas; Firmansyah, Firmansyah (Al-Mizan (e-Journal), 2025)
Social transformation and the increasing economic participation of women have significantly reshaped the role of wives in muslim households. In the context of prevailing social transformations and the escalating economic participation of women, the role of wives has undergone a shift, no longer confined to the management of household finances but extending to the realm of investment decision-making and long-term financial planning. It is therefore vital to possess fundamental financial literacy, i.e. the capacity to differentiate between needs and wants. The role of the wife as a competent financial manager has been demonstrated to have a significant impact on the economic stability and well-being of the family unit. The present research employs a qualitative method, adopting a literature review approach to examine various sources on Islamic jurisprudence, Islamic economic policies, and empirical studies related to women's financial roles in households. The findings reveal a persistent gap in understanding the financial rights and responsibilities of wives in Islam, particularly concerning the concepts of financial support (nafakah) and asset ownership. Moreover, the dearth of Islamic financial literacy engenders a substantial challenge in the implementation of Islamic economic principles within Muslim families. Consequently, the provision of comprehensive financial education, the implementation of policies that support women's financial roles, and the promotion of open communication between spouses are imperative to establish a fair financial management system in accordance with Islamic principles